2016
DOI: 10.1002/app.43962
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of spinneret geometric effect on spinning dynamics of dry‐jet wet‐spinning of cellulose/[BMIM]Cl solution

Abstract: In this study, the effect of spinneret geometry, including the entrance angle a of the entrance channel, the length L s , and the diameter D 0 of the exit channel, on the spinning dynamics of dry-jet wet-spinning of cellulose/1-butyl-3-methylimidazolium chloride ([BMIM]Cl) solution was simulated by using finite element method. Based on the mathematical model of dry-jet wet-spinning established in our previous work (Xia et al., Cellulose 2015, 22, 1963 the radial and axial profiles of velocity, pressure, and sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…Consequently, the converging brous network is more highly aligned within the P500 lm, leading to a denser network of rigid bonds, and the lm is unable to stretch as much as the P300 lm. The situation is analogous to ow convergence just before the entrance region in a spinneret 34 .…”
Section: Mechanical Response Of Templated Nanopillar Filmsmentioning
confidence: 99%
“…Consequently, the converging brous network is more highly aligned within the P500 lm, leading to a denser network of rigid bonds, and the lm is unable to stretch as much as the P300 lm. The situation is analogous to ow convergence just before the entrance region in a spinneret 34 .…”
Section: Mechanical Response Of Templated Nanopillar Filmsmentioning
confidence: 99%
“…Явление разбухания струи известно и достаточно хорошо изучено в теории и практике экструзии растворов или расплавов полимеров. Суть эффекта заключается в увеличении диаметра струи материала в 3-4 раза по отношению к диаметру выходного отверстия фильеры [5][6][7]. После выхода материала из фильеры образующийся стержень имеет внешний диаметр больший, чем диаметр отверстия фильеры.…”
Section: химическая технологияunclassified
“…From the previous discussion, it is seen that a mathematical model for the spinning process is useful for understanding the relationship between the spinning conditions and fiber properties [17,18]. Recently Xia et al [2,4] suggested a full 3-D model to predict numerically the fiber diameter along the spinning line, and important information was revealed. The numerical results can be used for optimal design of the spinning process, however, numerical simulation can not pick out an explicit relationship among spinning conditions, spinneret structure, and fiber properties.…”
Section: --------------mentioning
confidence: 99%
“…As shown in fig. 1 the dry-jet wet spinning process is described in [4]. The spinning solution enters the spinneret.…”
Section: One-dimensional Modelmentioning
confidence: 99%
See 1 more Smart Citation